Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 85372416 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Magnoliophyta", "TaxonKey is Plantae" ] }, "HasGeospatialIssue is false", "HasCoordinate is true", "Year is greater than or equal to 1950" ] } The dataset includes 85372416 records from 2301 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002169-160311141623029/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences